RELACIÓN DE LA SALUD ORAL CON LAS ENFERMEDADES CRÓNICAS EN LAS PERSONAS MAYORES: UNA REVISIÓN (2018)
The relationship between oral cavity and general health is evident; certain chronic pathologies have a greater impact on the bucodental condition and some oral diseases generate greater damage at systemic level. Thus, diabetes, osteoporosys, cancer, and cardiovascular and neuro-psyquiatric medication, among others, affect the oral condition. On the other hand, periodontitis, edentulism, oral pain and oral cancer affect the general health. These associations raise the necessity of a greater investigation and the responsibility that has all the health professionals to implement oriented actions to promote the health and to prevent the disease with an integral vision of the people.